Outsourcing secure two‐party computation as a black box. Issue 14 (20th March 2016) - Carter, Henry; Mood, Benjamin; Traynor, Patrick; Butler, Kevin
Abstract: Secure multiparty computation (SMC) offers a technique to preserve functionality and data privacy in mobile applications. Current protocols that make this costly cryptographic construction feasible on mobile devices securely outsource the bulk of the computation to a cloud provider. However, these outsourcing techniques are built on specific secure computation assumptions and tools, and applying new SMC ideas to the outsourced setting requires the protocols to be completely rebuilt and proven secure. In this work, we develop a generic technique for lifting any secure two‐party computation protocol into an outsourced two‐party SMC protocol. By augmenting the function being evaluated with auxiliary consistency checks and input values, we can create an outsourced protocol with low overhead cost. Our implementation and evaluation show that in the best case our outsourcing additions execute within the confidence intervals of two servers running the same computation and consume approximately the same bandwidth. In addition, the mobile device itself uses minimal bandwidth over a single round of communication. This work demonstrates that efficient outsourcing is possible with any underlying SMC scheme and provides an outsourcing protocol that is efficient and directly applicable to current and future SMC techniques. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this work, we develop a protocol for outsourcing secure multiparty computation (SMC) protocols as a black box. By adding consistency checks to the underlying evaluated function, we can turn any two‐party SMC protocol into an outsourced protocol. Our implementation and performance evaluation demonstrate that the overhead incurred by outsourcing on the cloud is negligible and allows for practical applications to be executed from a mobile device in a privacy‐preserving manner.